Dance, Music, and Literature as Didactic Strategies for Intercultural Dialogue in the Andean Region - Cabal Pérez, Cindy Johanna (2023)
Currently, there is a growing uprooting by culture, dance, music, ancestral knowledge, and the idiosyncrasy that characterizes the Colombian regions, particularly, the Andean region. This leads to some traditions and customs not being transmitted and therefore preserved. Therefore, the researchers consider it necessary to implement actions in the classroom that allow, through dance, music, and literature, to promote the cultural recognition of this region. As the main objective of this research, the investigators aim to generate an intercultural dialogue that permits the development of cultural identification and recognition through dance, music, and literature of the Andean region in the departments of Cundinamarca and Nariño, in the educational institutions Juan Luis Londoño de la Cuesta and the Encano Municipal Educational Institution. For data collection, the researchers employed three techniques: survey, direct observation, and interview. A survey with a questionnaire of nineteen closed questions was applied to identify the knowledge that the students had about the culture of the department in which they do not live. In addition, direct observation and interviews were carried out to complement the information obtained through the survey. Therefore, the authors created spaces with different students from two institutions, where an intercultural dialogue took place, and through which the identification and recognition of the culture of the Andean region was promoted. The study of this research yielded significant results; for instance, the students reached a deeper understanding of the disciplines, as well as being more participatory and less shy. As a recommendation, the investigators suggest to continue with the integrated teaching of these disciplines, promoting collaboration between educational institutions and taking advantage of technology as a means to enrich the experience.